Analisis penyerapan tenaga kerja sektor industri dan faktor-faktor yang mempengaruhinya di Provinsi Jambi - Redi Hermansyah; Arman Delis; Etik Umiyati (Prodi Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Jambi, 2021)
This study aims to: 1) To analyze the development of industrial sector GRDP, UMP, and the number of companies in Jambi Province. And 2) To analyze what factors influence the absorption of labor in the industrial sector in Jambi Province by using panel data regression analysis tools. Based on the development of the GRDP of the industrial sector and the provincial minimum wage, it continues to increase every year, as well as the variable number of companies that fluctuates every year. Based on the results of the F test, it can be concluded that the GRDP of the industrial sector, the provincial minimum wage, and the number of companies jointly have a significant effect on employment in the industrial sector because the probability is less than 0.001. Based on the results of the t-test, it can be concluded that the variables that affect employment in the industrial sector are the GRDP of the industrial sector and the number of companies because the probability is less than 0.05. Keywords: Absorption of labor in the industrial sector, GDP, Provincial minimum wages and number of companies.